2014
DOI: 10.14222/turkiyat1235
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul 4. Sınıfta Uygulanan Yaratıcı Drama Etkinliklerinin Öğrencilerin Yaratıcılık Düzeylerine Etkisi

Abstract: Bu araştırmanın amacı, yaratıcı drama etkinliklerinin ilkokul 4. sınıf öğrencilerinin yaratıcılık becerilerinin gelişimine etkisini incelemektir. Araştırmada ön test-son test kontrol gruplu deneysel desen kullanılmıştır. Çalışma gurubunu Erzurum'da bulunan Aydın Doğan İlköğretim Okulu 4-A ve 4-B sınıf öğrencileri oluşturmaktadır. Çalışma grubunda 17 kontrol, 17 deney olmak üzere 34 öğrenci yer almıştır. Veri toplama aracı olarak 1977'de Raudsepp tarafından geliştirilen ve Çoban (1999) tarafından Türkçeye uyarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Aral (1999) in his study in conservatory students found that the mean score of adolescents training in arts in the scale of creativity was meaningfully higher than the scores of adolescents who are not trained in arts. Ulaş et al (2014), in their study in fourth year-students of primary school level using the Raudsepp Creativity test found that creative drama activities had a positive effect on the creativity levels of students. It can be concluded that the creative activity program supported with musical activities can promote creativity.…”
Section: Discussionmentioning
confidence: 96%
“…Aral (1999) in his study in conservatory students found that the mean score of adolescents training in arts in the scale of creativity was meaningfully higher than the scores of adolescents who are not trained in arts. Ulaş et al (2014), in their study in fourth year-students of primary school level using the Raudsepp Creativity test found that creative drama activities had a positive effect on the creativity levels of students. It can be concluded that the creative activity program supported with musical activities can promote creativity.…”
Section: Discussionmentioning
confidence: 96%